(untitled) (Review of Croatian History, 2021)
This paper analyses the way in which Dr Franjo Tuđman is depicted in the textbooks used in Croatian schools. The author concludes that while some basic biographical data are provided, with respect to his contribution as a statesman some authors are prone to politicization and even self-censorship, the intention of which is to diminish his contribution to the history of the Croatian people. Most issues concerning internal and external policies require further research.